2021
DOI: 10.6118/jmm.20028
|View full text |Cite
|
Sign up to set email alerts
|

The Largest Uterine Leiomyoma Removed by Robotic-Assisted Laparoscopy in the Late Reproductive Age: A Case Report

Abstract: Uterine leiomyoma is a very common gynecological tumor in the reproductive years. Recent studies have shown that surgical treatment of uterine leiomyoma using robotic-assisted laparoscopic myomectomy (RALM) is associated with significantly fewer complications, lower estimated blood loss, fewer conversions, and less bleeding than conventional laparoscopic myomectomy. This study reports the case of a giant uterine leiomyoma treated using RALM. A 50-year-old woman was referred to our outpatient clinic with progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several case studies show the enucleation of huge myomas (the biggest being 28 cm and 3.2 kg), while pushing the limits of robotic assisted techniques [25,26] . These cases confirm the efficiency, reliability, and safety of the robotic approach in well-selected cases regardless of the size of the fibroids.…”
Section: Large/heavy/multiple Myomasmentioning
confidence: 99%
“…Several case studies show the enucleation of huge myomas (the biggest being 28 cm and 3.2 kg), while pushing the limits of robotic assisted techniques [25,26] . These cases confirm the efficiency, reliability, and safety of the robotic approach in well-selected cases regardless of the size of the fibroids.…”
Section: Large/heavy/multiple Myomasmentioning
confidence: 99%
“…Robot-assisted laparoscopic myomectomy (RALM) has been suggested as an effective surgical method, with comparable surgical outcomes to laparoscopic myomectomy [ 8 ]. Our group previously reported that RALM could be successfully performed in a patient with a myoma as large as 28 cm [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…With great deal of interest we read the article entitled: “The Largest Uterine Leiomyoma Removed by Robotic-Assisted Laparoscopy in the Late Reproductive Age: A Case Report” by Jeong et al [ 1 ].…”
mentioning
confidence: 99%